2015
DOI: 10.7287/peerj.preprints.655v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood, sweat and tears: non-invasive vs. non-disruptive DNA sampling for experimental biology

Abstract: may be necessary to obtain DNA from an organism before using it in a bioassay or an experiment, to identify and distinguish between cryptic species, or when comparing different morphocryptic genotypes. Another example could be the assessment of relatedness between organisms prior to a behavioural study. In such cases, DNA must be obtained without affecting the fitness or behaviour of the subject being tested, as this could bias the results of the experiment. This points out the existence of a gap in the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…For aquatic vertebrates relying on external fertilizations (e.g. most fishes and frogs) monitoring reproductive activity can be achieved by destructive, injurious or non-invasive methods (Table 1) (Lefort et al 2015). The extra mortality rate imposed by destructive sampling methods makes them undesirable for monitoring reproduction in rare and threatened species (Tsukamoto 2006;Wei et al 2009;Engstedt, Engkvist & Larsson 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For aquatic vertebrates relying on external fertilizations (e.g. most fishes and frogs) monitoring reproductive activity can be achieved by destructive, injurious or non-invasive methods (Table 1) (Lefort et al 2015). The extra mortality rate imposed by destructive sampling methods makes them undesirable for monitoring reproduction in rare and threatened species (Tsukamoto 2006;Wei et al 2009;Engstedt, Engkvist & Larsson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Non-exhaustive list of categories for monitoring methods that can be used to monitor reproductive activity in aquatic vertebrates relying on external fertilization. Definitions for the different categories were modified fromLefort et al (2015) …”
mentioning
confidence: 99%
“…Non-lethal techniques have been developed to extract insect DNA from frass (feces) and exuviae (shed exoskeleton) [8,9]. This approach is particularly useful for insects at the larval stage of development, where large quantities of frass are generated, or when instars shed their exoskeletons [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is particularly useful for insects at the larval stage of development, where large quantities of frass are generated, or when instars shed their exoskeletons [10,11]. Before using an organism in a bioassay to distinguish between cryptic species, to differentiate cryptic morphs, or assess relatedness between organisms before a behavioral study, DNA must be obtained without affecting the fitness or behavior of the organism [8]. However, the detection rate is not high with these methods due to degradation of DNA by nucleases in frass or exuviae samples collected in the field [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to disruptive survey methods, such as gill netting or the usage of toxins, eDNA methods are less disruptive for the target species and ecosystems and can be used to survey the distribution of rare species (Jerde et al 2011;Lefort et al 2015). Recent studies have shown that eDNA analysis can be applied for specifying the breeding season or spawning activity by monitoring the change in eDNA concentration or ratio of nuclear to mitochondrial eDNA markers (Spear et al 2014;Erickson et al 2016;Buxton et al 2017;Bylemans et al 2017).…”
Section: Introductionmentioning
confidence: 99%